"CLITEMNESTRA" MEJOR QUE "CLITEMESTRA" - Ruiz de Elvira Prieto, Antonio (Myrtia, 2001)
In this paper the arguments are minutely examined which in the XIXth and XXth centuries have been alleged and maintained by a great number of scholars, some favouring the spelling ’Clytaemestra’ without -n-, the others, on the contrary, the spelling ’Clytaemnestra’ with -n-. The author proves that the latter spelling, vid. the one with -n-, is largely preferable.